Comparative study on numerical simulation based on CALPUFF and wind tunnel simulation of hazardous chemical leakage accidents - Zhang, Rongqian; Li, Mei; Ma, Hancong (Frontiers in Environmental Science, 2022)
CALPUFF, as a Lagrangian puff modeling system, is mostly used in the field of atmospheric environment research and risk assessment. CALPUFF performs well for short-term and short-range release scenarios over complex terrain, as well as long-term and long-range transportation. Therefore, this article uses the CALPUFF model to simulate a toxic gas leakage accident in a hazardous chemical plant in an urban area, focusing on the influence of local buildings. Wind tunnel experiments are performed in accordance with the CALPUFF experiments to assess the model’s accuracy in cases of chemical leakage accidents. The results of the wind tunnel experiment are superimposed on the map of CALPUFF calculation, and the quantitative analysis is also performed. The comparative results show that the simulation results of the CALPUFF are mainly affected by factors such as wind direction, wind speed, and the complexity of the surface environment. With less influence of buildings, such as the south and north wind, the CALPUFF simulation is consistent with the wind tunnel experiment, having a correlation coefficient of over 0.7 in most cases, while under the east wind, the consistency is significantly lower due to the influence of buildings. In addition, it is found that the wind tunnel experiment is more accurate in the near field of the pollution source, while CALPUFF is more suitable for simulating the overall trend of gas dispersion. The comparison and evaluation of the capabilities of different methods on gas dispersion simulation are helpful in guiding the emergency response during hazardous chemical leakage accidents.